Engineering human bone marrow-derived mesenchymal stromal cell aggregates for enhanced extracellular vesicle secretion in a vertical-wheel bioreactor - Berry, Danyale; Boirie, Breana; Singh, Mandip; Sun, Li; Jung, Sunghoon; Li, Yan; Zeng, Changchun (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionHuman mesenchymal stem/stromal cells (hMSCs) hold significant regenerative potential due to their anti-inflammatory and pro-angiogenic secretome. Three-dimensional (3D) hMSC aggregates secrete extracellular vesicles (EVs) with enhanced immunomodulatory properties compared to 2D cultures. However, the clinical translation of hMSC-EVs remains limited by low production yield. This study investigates scalable EV generation from 3D hMSC aggregates in a novel Vertical-Wheel Bioreactor (VWBR), leveraging shear stress-mediated biochemical cues to enhance EV biogenesis and cargo relevant to nerve regeneration.MethodsBone marrow-derived hMSCs were cultured as 3D aggregates in VWBRs and exposed to two different culture media—αMEM/FBS (serum-containing) and DMEM/F12/B27 (serum-free)—under three agitation speeds (25, 40, and 64 rpm). Metabolite analysis and qRT-PCR were performed to assess metabolic activity and EV biogenesis, focusing on ESCRT machinery markers. EVs were isolated and evaluated for yield, size, markers, and microRNA cargo. Functional assays were conducted to measure the effects on EVs on Schwann cells under LPS-induced neural inflammation.ResultsVWBR culture resulted in increased expression of EV biogenesis genes and glycolytic pathway markers compared to static culture. The αMEM/FBS (serum-containing) condition was more robust than DMEM/F12/B27 (serum-free) condition. EV yield (EV number per cell) increased by 3-10 fold (in serum-containing medium) in VWBR compared to static culture, with particle sizes ranging from 120-180 nm and appropriate EV marker expression. microRNA-sequencing showed upregulation of miR-29a-3p, miR-451a, miR-224-5p, miR-16-5p, miR-133a-3p, and miR-143-3p, indicating enhanced EV biogenesis, metabolic reprogramming, and immunomodulatory potential. Functionally, VWBR-derived EVs modulated inflammatory gene expression in Schwann cells exposed to LPS.DiscussionVWBR-driven hydrodynamics promotes EV biogenesis from 3D hMSC aggregates, improving metabolic activity, EV cargo relevance, and functional efficacy. The resulting EVs exhibit therapeutic cargo capable of modulating neural inflammation. These findings advance understanding of dynamic aggregation on metabolic cues and EV production, demonstrating a scalable strategy for generating therapeutically potent hMSC-EVs for neuropathic and regenerative applications.